Faktor-faktor yang Mempengaruhi Pertumbuhan Pasca-Sapih Kambing Boer dan Persilangannya pada Populasi Peternakan Tertutup - Nugroho, Tristianto; Widyas, Nuzul; Widi, Tri Satya Mastuti; Prastowo, Sigit (Universitas Bengkulu, 2023)
This study aimed to analyze the factors affecting the post-weaning growth of Boer and Boer cross goats in a closed breeding farm population. A total of 1,083 female kids were selected from a record of 1,501 weaned kids produced by mating Boer bucks with Boer does, Jawarandu does, and Boer × Jawarandu does. The data collected at a private company's goat farm represent a closed breeding population from January 2013 to January 2016. The data were selected based on the weaning weight and at least one post-weaning weight at approximately 6, 9, or 12 months. Two-step linear models were applied: complete model and reduced model. The complete model factors included genetic group, buck, litter size, birth season, weaning season-year, and their interactions. The reduced model included only significant factors and two-way interactions. The results showed that the genetic group, bucks, litter size, birth season, and weaning season-year significantly affected Boer and Boer cross goats' post-weaning weight and average daily gain. Additionally, interactions between the genetic group with the buck, litter size, and birth season were observed. In conclusion, genetic and non-genetic factors significantly influence the post-weaning growth of Boer and Boer cross goats. Non-genetic factors should be considered in the model and selection to achieve optimal goat performance.